effect of ascorbic acid on gel formation of myofibril from big eye scad fish (Selar crumenophthalnus) - Achmad Subagio; Wiwik siti Windrati; Mukhamad Fauzi; Yuli Witono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Effect of ascorbic acid on gel formation of myofibril from big eye scad fish (Selar crumenophthalnus)were studied for its development as food ingredient. Myofibril was galled by the addition of various concentrations of ascorbic acid (0, 0.1, 0.2, 0.3 and 0.4%) and the gels were then characterized for its cooking loss, of the gel, but at 0.4% the cooking loss of gel increased significantly. Accordingly, the WHC of the gel changed insignificantly with the ascorbic acid addition below 0.3%, and decrease sharply in the addition of 0.4%. Gel textures were affected by the addition of ascorbic acid at all levels, namely 29.9 ± 1.9, 31.0 ± 0.3, 35.4 ± 0.4, 46.7 ± 1.5, and 115.7 ± 3.2 g/7 mm for 0, 0.1, 0.2, 0.3 and 0.4%, respectively. Sodium dodecyl sulfate – polyacrylamide gel electrophoresis (SDS-PAGE) showed that addition of ascorbic acid drove formation odfdisulphide bond in the myosin heavy chain (MHC) and other myofirillar proteins, resulting in the development of a strong three dimensions structure I myofibril gel as shown by microscopic structure. Key words : Ascorbic acid, Big eye Scad Fish (Selar crumenophthalnus), el formation myofibril